Accumulation and contamination assessment of heavy metals in sediments of commercial aquaculture farms from a coastal area along the northern Bay of Bengal - Hossain, Mohammad Belal; Sultana, Jakia; Pingki, Farjana Haque; Nur, As-Ad Ujjaman; Mia, Md. Shoaib; Bakar, Muhammad Abu; Yu, Jimmy; Paray, Bilal Ahamad; Arai, Takaomi (Frontiers in Environmental Science, 2023)
Heavy metal contamination in aquaculture farm sediment may create a major risk to ecosystem and human health via the food web as a result of poor handling, incorrect waste management, and extensive use of artificial feed to increase yield and make profit. In this study, heavy metals (e.g., Cd, Cr, Pb, Cu, Zn, Mn, and Ni) were analyzed to examine the accumulation, sources, and contamination levels from the bottom sediment samples in 12 different commercial aquaculture farms from a South Asian coastal area using atomic absorption spectrometer (AAS). The findings revealed that the mean concentrations of heavy metals (µg/g) followed the decreasing order of Mn (48.75±6.75) > Zn (7.09±2.61) > Ni (6.85±2.08) > Cr (5.01±1.04) > Cu (3.00±0.54) > Pb (2.77±0.80) > Cd (0.22±0.07). Contamination factor (CF < 1) and geo-accumulation index (Igeo < 0) for all metals implying the unpolluted status of fish farms by heavy metals. The mean pollution load index (PLI) was found 0.11 refereeing to very low level of contamination. Positive significant correlations (p < 0.05) between Cu-Cr (r=0.65), Mn-Cd (r=0.594), Zn-Pb (r=0.591), Zn-Cu (r=0.586) and Zn-Cr (r=0.757) indicated their similar sources of origin. Multivariate analysis like cluster analyses (CA) and principal component analysis (PCA) specified that Cr, Cu, and Zn might have anthropogenic sources. Therefore, future research is recommended to determine element mobility from the feed to pond sediment and fish, and thereby reduce environmental risk to ecosystem and human health.